“Gelungan” Characters of Kamasan Puppet in the Magala-Gala Tradition Game - Putra, I Made Pande Agus Cahyadi; Budiarta, I Dewa Putu Gede; Jodog, I Made (Program Studi Seni Murni ISI Bali, 2024)
Feudalism, which is a social or political system that gives great power to the nobility, in Indonesia, especially in Bali, still adheres to this system, where in literature and in traces of discourse it is stated that this system was already in effect at that time. However, apart from the Feudal system, Indonesia, especially Bali, has many existing traditions, such as the art of wayang kamasan painting and also Ma-gala-galaan or Gala-gala. The techniques used in the process of creating works of painting are the Dussel and Sigar techniques and how to visualize them on plywood media. The method used in the creation process is Hawkins, which consists of three stages, namely idea exploration, improvisation, and realization or forming.The result of this method is to search for ideas and how to visualize the concept of the Gelungan Wayang Kamasan character on plywood media. Improvise to find harmonious proportions and colors. The manifestation (forming) of all visual results found related to the title adopted is undergoing development. With the creation of this work, it is hoped that it will be useful for the community related to this state system and also about traditional painting and traditional games in Bali.